Tigers in their new territory: intraspecific interactions among the reintroduced tiger population in Panna Tiger Reserve, Central India - Supratim Dutta; Ramesh Krishnamurthy (Scientific Reports)
Abstract Intra-specific interactions among top carnivores are among the most intriguing behavioural aspects and essential components of population dynamics. Static interactions pertain to space use, while dynamic interactions involve spatio-temporal patterns influenced by social structure, distribution, mate selection, and density. Previous studies have focused on static interactions, successfully estimating spatial overlap but leading to a knowledge gap of dynamic interaction to be able to compute attraction and avoidance on similar spatio-temporal scales. We fitted VHF and GPS collars to 13 tigers to study the static and dynamic interactions among the reintroduced tiger population in Panna Tiger Reserve. To investigate spatial interactions, we used Autocorrelated Kernel Density Estimator methods. To capture dynamic interactions at different scales, we calculated Benhamou’s Movement Interaction index and a Correlation Coefficient (Cr) at two critical distance thresholds (Δ500m and 100m). We documented 18 and 35 intra-sex dyads for males and females respectively, and 73 inter-sex dyads from 2009 to 2019. We observed high spatial overlap in male*female dyads. Dynamic interactions and similar movement patterns were noted in mother*cub dyads, while male movements were predominantly independent. We evaluated 23 male*female dyads and found moderate to strong dynamic interactions between individuals. Spatial interaction largely depends on home-range shape and size and does not necessarily affect dynamic interaction. Males and females moved independently to avoid intra-guild competition, exhibiting unsynchronized movement patterns. However, interaction was infrequently recorded, primarily during mating. Female siblings showed philopatry and preferred to move jointly before establishing their own territories. Initially, founder females had limited choice for mate selection with only one male, but as more males became available, females exhibited clear and consistent mate selection. This indicates that founder populations for reintroduction should include adequate mate choices.